2014
DOI: 10.1186/1475-2875-13-498
|View full text |Cite
|
Sign up to set email alerts
|

Fixed dose artesunate amodiaquine – a phase IIb, randomized comparative trial with non-fixed artesunate amodiaquine

Abstract: BackgroundPharmacokinetic (PK) and pharmacodynamic (PD) data are limited for artesunate (AS) and amodiaquine (AQ) in uncomplicated Plasmodium falciparum.MethodsFrom 2007-8, 54 P. falciparum-infected, Kenyan adults were assigned randomly fixed dose (FD) ASAQ (n = 26) or non-fixed (NF) ASAQ (n = 28). Total doses were 600 mg AS (both arms) + 1,620 mg (FD) or 1,836 mg (NF)AQ. Follow-up extended over 28 days. PK data were collected for AS, dihydroartemisinin (DHA), AS + DHA combined as DHA equivalents (DHAeq), AQ, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 58 publications
1
10
0
Order By: Relevance
“…Appetite increase was reported, at 40%, in our study compared to 33% for Nauclea pobiguinii and drowsiness was observed, also at 20%, for CoBaT-Y017 compared to 7% for Nauclea pobiguinii [14]. Moreover, the increased appetite would be favorable to fight anorexia, one of the symptoms of uncomplicated malaria [17]. There were neither life-threatening adverse events reported in this trial nor clinically significant adverse findings on vital signs, significant modification of biochemical, or haematological parameters attributable to CoBaT-Y017 .…”
Section: Discussionmentioning
confidence: 54%
“…Appetite increase was reported, at 40%, in our study compared to 33% for Nauclea pobiguinii and drowsiness was observed, also at 20%, for CoBaT-Y017 compared to 7% for Nauclea pobiguinii [14]. Moreover, the increased appetite would be favorable to fight anorexia, one of the symptoms of uncomplicated malaria [17]. There were neither life-threatening adverse events reported in this trial nor clinically significant adverse findings on vital signs, significant modification of biochemical, or haematological parameters attributable to CoBaT-Y017 .…”
Section: Discussionmentioning
confidence: 54%
“…Bazett’s and Fridericia’s were both reported in 10% ( n = 12) of trials. Five trials [ 18 , 31 , 37 39 ] used alternative formulae, including Wernicke et al’s [ 40 ], Hodges’ and Karen [ 41 ].…”
Section: Resultsmentioning
confidence: 99%
“…Our meta-analysis further confirms established relationships between the QT interval and the demographic factors of age and sex are relevant in malaria. The QT interval does not exhibit a sex difference in childhood [10] until around puberty, when it shortens in males but not females [28], then lengthens gradually in adulthood in males more than females [11]. This difference is thought to result from pubertal changes in sex hormone levels, although the underlying mechanisms are not fully understood [11].…”
Section: Discussionmentioning
confidence: 99%